Organisational Transparency and Teachers’ Job Performance in Ogun State Public Secondary Schools - Alaba, Adebola O.; Oguntimehin, Y. Abiodun (NIU Journal of Social Sciences; Vol 4 No 2 (2018): KIU Journal of Social Sciences, Vol. 4 No. 2, June 2018, 2018)
This study investigated Organisational transparency as determinant of teachers’ job performance in public secondary schools in Ogun State Nigeria. The study also sought to determine how organizational transparency affects the job performance of male and female teachers in the state. A total of 1037 teachers selected through multistage sampling procedure throughout 20 educational zones in Ogun state participated in the study. Data were collected with three instruments which were adapted, pilot tested and found to be reliable and valid. Multiple regression analysis was used to analyse the data collected. The results showed that Organisational transparency determined teachers’ job performance to a large extent. The variable was significant (P<0.05). Organisational transparency significantly determined teachers’ job performance. The variable also significantly determined male and female teachers’ job performance in Ogun state public secondary schools. The study therefore recommended that the principal should improve his openness, be honest, be beneficial to his/her workforce to gain their acceptance and trust in his/her school. Also principal should engage in activities that can enhance Teachers’ trust in principal. Organisational transparency as demonstrated by principals’ dealings is a vital factor in achievement of organisational goals. Keywords: Organisational transparency, Male teachers, female teachers, teaches’ job performance, secondary school.